A bifactor model for the Scale of Attitudes towards Statistics - Moral de la Rubia, José (2021)
The objectives of the study were to determine the psychometric properties of the Scale of Attitudes towards Statistics in Mexico. In this instrumental study, a non-probabilistic sample of 383 Mexican psychology students who responded to two attitude scales was analyzed. The bifactor model with three specific factors (safety, pleasure-usefulness, and motivation) showed the best properties of fit and convergent validity. The average attitude was neutral and more positive in men than in women. The general factor had a high correlation with attitude towards research. It is concluded that the three-factor bifactor model represents the relationship between the items better than the original five-factor model.